2022
DOI: 10.56557/bn/2022/v42i11548
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Carbon Stocks in the Dimako Communal Forest, East-Cameroon

Abstract: In the global context of global warming, Cameroon's forests have a major role to play in mitigating climate change. The objectives of this study were to assess and spatialize carbon stocks in different types of land use/land cover types. To achieve these objectives, an approach based on the diachronic analysis of satellite images and the inventory of woody plants with a diameter greater than or equal to 10 cm in plots of 250 m x 20 m were carried out. The results show a 22.94% decrease in the area of mature fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…The AGB had the highest Carbon stock in this study. Similar results were obtained by Hubert et al [35] in the Dimako communal forest in the East region of Cameroon. Vahedi et al [100] indicated that the trunk biomass is higher than the other compartments of the tree.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The AGB had the highest Carbon stock in this study. Similar results were obtained by Hubert et al [35] in the Dimako communal forest in the East region of Cameroon. Vahedi et al [100] indicated that the trunk biomass is higher than the other compartments of the tree.…”
Section: Discussionsupporting
confidence: 90%
“…Unfortunately, no real attempts have been made to estimate the state of biomass in most African forests, as estimating change in biodiversity and Carbon stock became difficult [30] in Africa in general and Cameroon in particular [31]; creating considerable uncertainty about the above-and belowground quantity and distribution of carbon stocks in African forests [32]. This study is one of few in Cameroon and the broader Congo Basin region that has calculated diversity, above-ground biomass, and carbon in a semi-deciduous forest [32] [33] [34] [35]; as despite the importance of this forest reserve, its biodiversity, Carbon storage capacity, the relationship between tree diversity and their ability to store Carbon remains poorly known.…”
Section: Introductionmentioning
confidence: 99%
“…The latter, because of its rich diversity of commercially important tree species and relatively small area, is more threatened than the dense evergreen forest. These forests are important reserves of genetic, specific and ecosystem diversity that should be conserved as much as possible for the sustainable management of this biological heritage [ [6] , [7] , [8] ]. These forests provide multiple services [ 9 , 10 ], contribute to the regulation of the greenhouse effect and the establishment of major climatic balances [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%